Effect of Fluoride Gel on Microhardness of Flowable Composites: An In Vitro Study - Rashidian, Ali; Saghiri, Mohammad-Ali; Mohammad Bigloo, Sanaz; Afsharianzadeh, Maryam (Journal of Dental School, 2019)
Objective: Adequate knowledge about restorative materials particularly flowable composite resins with favorable physical properties like optimal microhardness and resistance to environmental factors is a big concern for many dentists. Flowable composites have several applications for fissure sealant therapy and preventive resin restorations (PRR); which are common treatments in pediatric dentistry. Acidulated Phosphor Fluoride (APF) topical gels can cause surface degradation and weight loss in composite resins and decrease their wear resistance. This study aimed to assess the effect of APF gel on the microhardness of flowable composites. Methods: This experimental in vitro study was conducted on 60 specimens measuring 2mm in thickness and 6mm in diameter fabricated of Tetric N-Flow (Ivoclar-Vivadent), PermaFlo (Ultradent) and Denfil (Vericom) flowable composites (n=20 for each group). Specimens were stored in artificial saliva at room temperature for one week. The 20 specimens in each group were randomly divided into 2 subgroups of test and control (n=10). Microhardness was measured using Vickers microhardness tester. In the control groups, 3 indentations were made on each disc on the periphery of a circle with at least 1mm distance from one another and from the specimen margin. The mean microhardness value was then calculated. The mean of all measurements was calculated as well. Test specimens were subjected to (Sultan) 1.23% APF gel for 4min and then rinsed and air- dried. Their microhardness was measured again as described above. Two-way ANOVA was used to compare the effect of APF gel and type of composite on the microhardness of different flowable composites. Results: Based on the results, the microhardness of Denfil, PermaFlo and Tetric N-Flow was 16.5 (1.32), 37.36 (2.13) and 20.39 (0.52) before and 16.46 (2.20), 35.04 (2.43) and 19.13 (2.20) after the application of APF gel, respectively. The difference between the before and after values for each composite was significant (p=0.193) while the difference between different composites was statistically significant in this regard (p<0.001). Conclusion: Exposure of Denfil, PermaFlo and Tetric N-Flow flowable composites to APF gel for 4min had no effect on their microhardness.